Influence of work and tool materials on parameters of electrical discharge machining(EDM) - Amin, A. K. M. Nurul; Sarder , A. K. (IIUM Press, 2002)
Influence of the properties of work and tool materials on material removal rate (MRR), tool wear ratio (TWR), thickness of the recast layer, surface roughness and accuracy of machining in EDM process has been investigated. Copper brass, stainless steel, mild steel and grey cast iron have been used in various combinations as work and tool materials. From the experimental results it is found that MRR slows down with machining time. Apart from that it has been found that MRR and TWR are inversely proportional to the melting points of the work and tool materials respectively. Electrical conductivity of the tool material also has appreciable influence on tool wear ratio. Wear ratio was found to be minimum in the case of the copper electrode having maximum electrical conductivity. It has been also observed that for all combinations of work and tool materials, a recast layer is formed on the machined surface. It has been observed that the micro cavities formed in the cases of lower melting point electrode materials like copper and brass having higher electrical conductivity are comparatively smaller in size (2-3 μm) as compared to the sizes of the micro cavities (8-20 μm) formed in the cases of high melting pointer electrodes having also lower electrical conductivity. Consequently the machined surface roughness produced in the latter cases is higher. It has been also observed that the debris concentration increases due to side sparking of the electrode. The tendency of debris concentration is the maximum at the middle of the tool¬job interface resulting in high bottom surface inaccuracy, specially when high melting point work materials are machined with electrodes like brass having low melting point and relatively lower electrical conductivity. From the point of view of MRR, brass electrodes have been found to be the most suitable tool, but from the point of view of machining accuracy and surface finish copper electrodes were found to yield the best result for the given set of job materials. So it was concluded that brass electrodes should be recommended for rough machining and copper electrodes for finish machining of the given work materials.